Guidelines for vapor cloud explosion, pressure vessel burst, BLEVE, and flash fire hazards. (Wiley, 2010)
This guide provides an overview of methods for estimating the characteristics of vapor cloud explosions, flash fires, and boiling-liquid-expanding-vapor explosions (BLEVEs) for practicing engineers. It has been updated to include advanced modeling technology, especially with respect to vapor cloud modeling and the use of computational fluid dynamics. The text also reviews past experimental and theoretical research and methods to estimate consequences. Heavily illustrated with photos, charts, tables, and diagrams, this manual is an essential tool for safety, insurance, regulatory, and engineeri.
Keywords: Chemical plants -- Fires and fire prevention.; Chemical plants -- Safety measures.; Pressure vessels -- Safety measures.; Chemicals -- Fires and fire prevention.; Explosions -- Prevention.; elektronické knihy; electronic books